Ab initio invesgations of the electronic and magnetic behavior of 1x1-MnN/GaN superlattice under hydrostatic pressure. (November 2019) - Espitia Rico, M J; Ortega López, C; Salcedo Parra, O
Abstract: In this paper, Ab-initio calculations are reported on the electronic and magnetic behavior of a 1x1-MnN/GaN superlattice in the wurtzite structure under hydrostatic pressure. The calculations were performed using the formalism of density functional theory with the generalized gradient approximations in the Perdew, Burke and Ernzerhof model, as well as the Wien2k computational package. The density of state shows that the electronic structure and the magnetic moment are affected by the hydrostatic pressure, because there is an abrupt change in the magnetic moment, which goes from 0 to 2.86 μβ /cell under a pressure of ∼ 24.45 GPa. When the pressure decreases to 0 GPa, the magnetic moment of the superlattice rises to 4.0 μβ /cell. Therefore, the superlattice exhibits a half-metallic behavior for a pressure of 0 GPa, while it acquires a metallic behavior when pressure surpasses 24.45 GPa.